2010
DOI: 10.4314/bajopas.v3i1.58558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing on the mineral content, proximate composition and phytochemical factors of the seeds of bauhinia monandra (kurz)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…The results of the minerals composition Table (4), showed the mineral composition Senna occidentalis Root, high concentrations values were found in potassium (43 mg/l or ppm) followed by phosphorous (28.5 mg/l), calcium (15 mg/l), sodium (3.65 mg/l) and magnesium (0.145mg/l). Similar ndings were reported by Agbugui,, et al [40]. In the other species of the same family.…”
Section: Physiochemical Anaylsissupporting
confidence: 91%
“…The results of the minerals composition Table (4), showed the mineral composition Senna occidentalis Root, high concentrations values were found in potassium (43 mg/l or ppm) followed by phosphorous (28.5 mg/l), calcium (15 mg/l), sodium (3.65 mg/l) and magnesium (0.145mg/l). Similar ndings were reported by Agbugui,, et al [40]. In the other species of the same family.…”
Section: Physiochemical Anaylsissupporting
confidence: 91%
“…Several studies have been conducted on the pharmacological activities of B. monandra extracts (Argolo et al, 2004;Macedo, 2008;Agbugui et al, 2010;Starr and Starr, 2011;Ajiboye et al, 2015), but no study was conducted on the effect of the B. monandra extract on platelet augmentation or to analyze its hematopoietic potential. However, a previous report revealed that a high content of iron in the extract may assist blood formation (Agbugui et al, 2010). Moreover, previous studies have also reported the use of other plants in platelet augmentation (Osime et al, 2008;Arollado and Osi, 2010;Apostol et al, 2012;Arollado et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the Yoruba tribe of South Western Nigeria, it is called "Abafe" (Ajiboye et al, 2015), and its decoction is taken to improve blood function, which is one of its health benefits. The tree is also fairly widely distributed throughout the natural grassland of Northern and South Eastern Nigeria (Agbugui et al, 2010). The leaf extract is bitter and traditionally used for the treatment of diabetes in Nigeria, Brazil (McCune and Johns, 2002), and Asia (Macedo, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The plant Bauhinia monandra is a leguminous tree with large leaves and pink flowers with red dots (Agbugui et al, 2010), commonly used in ornamental gardens (Anhwang et al, 2005), as nutritional source of vitamin A (Balogun & Fetuga, 1985) and in application to forage (Ilkiu-Borges & Mendonça, 2009). This plant is in general found in West Africa and India (Agbugui et al, 2010;Anhwang et al, 2005), but it also can be found in South America, especially in Brazil where it is indicated among other uses as a natural antidiabetic medicine (Menezes et al, 2007;Macêdo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The plant Bauhinia monandra is a leguminous tree with large leaves and pink flowers with red dots (Agbugui et al, 2010), commonly used in ornamental gardens (Anhwang et al, 2005), as nutritional source of vitamin A (Balogun & Fetuga, 1985) and in application to forage (Ilkiu-Borges & Mendonça, 2009). This plant is in general found in West Africa and India (Agbugui et al, 2010;Anhwang et al, 2005), but it also can be found in South America, especially in Brazil where it is indicated among other uses as a natural antidiabetic medicine (Menezes et al, 2007;Macêdo et al, 2008). According to studies disclosed in the literature, the utilization of Bauhinia monandra as well as several other species of this genus (Silva & Cechinel-Filho, 2002) as a hypoglycemic agent was possible because of the presence of flavonoids, such as a glycones or glycosides, which have been isolated from Bauhinia species (Cechinel-Filho, 2009;Menezes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%